Utilization of Papaya Seed Extract Lotion as a Skin Moisturizer - Syarifuddin, Aminah; Juliana, Iga; Sihombing, Yanna Rotua; Anggraeni, Ratih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
The skin plays a role in protecting bones and muscles, which are generally soft and elastic. In order for the skin to be well protected, internal and external care is needed. Internal skin care is obtained by consuming healthy foods. While external skin care is through the use of preparations directly on the skin. Several types of skin damage occur due to exposure to free radicals, such as exposure to UV rays. To avoid these dangers, a lotion that can act as an antioxidant is needed. Papaya seeds are rich in antioxidants that can increase skin moisture so that they are recommended as a basic ingredient for making lotion. The purpose of this socialization is to educate the public to be more concerned about health by using the right skin moisturizing lotion. PKM activities were carried out through socialization attended by 50 people around the Pantai Labu sub-district. The socialization material presented was about the use of papaya seed extract lotion as a skin moisturizer. The team also taught participants to be more careful in choosing cosmetics before using them. Increased knowledge was measured based on the pre-test and post-test values ??obtained from all participants. The results showed that there had been an increase in the knowledge of PkM participants, where the level of knowledge became high and very high with a percentage of 50% and 30%. Increased knowledge in the form of understanding about the preparation of papaya seed extract lotion that is stable and has a distinctive aroma. The lotion is also safe for the skin because the acidity level is appropriate and does not irritate the skin. This PkM activity has proven to have increased the understanding of PkM participants that lotions made from plant extracts are actually worthy of being used as an alternative for skin care.